Addressing Obesity in Aging Patients - Batsis, John A; Zagaria, Alexandra B (The Medical clinics of North America, 2018)
Obesity in older adults affects not only morbidity and mortality but, importantly, quality of life and the risk of institutionalization. Weight loss interventions can effectively lead to improved physical function. Diet-alone interventions can detrimentally affect muscle and bone physiology and, without interventions to affect these elements, can lead to adverse outcomes. Understanding social and nutritional issues facing older adults is of utmost importance to primary care providers. This article will also discuss the insufficient evidence related to pharmacotherapy as well as providing an overview of using physiologic rather than chronologic age for identifying suitable candidates for bariatric surgery.